Amorphous SiO2/C composite as anode material for lithium-ion batteries. Issue 9 (11th August 2017) - Cao, Linmin; Huang, Jilin; Lin, Zhipeng; Yu, Xiang; Wu, Xiaoxian; Zhang, Bodong; Zhan, Yunfeng; Xie, Fangyan; Zhang, Weihong; Chen, Jian; Meng, Hui
Abstract: Abstract : This work designed a facile preparation for an SiO2 /C composite as the anode material for lithium ion battery. Both SiO2 and carbon are amorphous. SiO2 and carbon are mixed uniformly. The SiO2 /C composite shows high specific capacity, cycle stability, and rate capability in lithium ion battery charge–discharge test. A stable reversible capacity of 1024 mA h/g at the current density of 100 mA/g is reached. The capacity retains 83% after 100 cycles. The uniform mixture of SiO2 and carbon leads to reduced volume change during the lithiation and delithiation of SiO2, together with the amorphous nature of SiO2 explains the high cycling stability. The carbon coating is a key factor for the high capacity and stability due to the increased electrical conductivity and reduced volume change. The resistance of the solid electrolyte interface film and charge transfer resistance of the SiO2 /C composite are much smaller than those of pure carbon, which is a direct proof of the improved conductivity of the material by the carbon coating.